(untitled) (ELang | An English Language Education Journal, 2021)
The title of this research paper is “The use of English songs to improve students’ pronunciation of interdental sound. This research was conducted at SMA Majalaya putra. Due to pandemic of Covid-19, the research was conducted online by using WhatsApp and Google Classroom. The purposes of this research were to identify The use of English songs to improve students’ pronunciation of interdental sounds and find out the students’ responses toward the use of songs in learning interdental pronunciation. The research applied a pre-experimental research method, then used one group pretest-posttest design to conduct the research. The study then chose 20 students of X Ipa 1 as the sample for experimental group. The instruments used in this research were pre-test, posttest and questionnaire. The data from pre-test and posttest were analyzed and calculated. According to the result of calculation, the value of t-observer was 11.7 then the freedom was 29 at the level of significance 0.05 for two tailed test is 2.093. Based on the calculation of t-observed, it was higher than the t-table. In other words, there was a significant different score before and after the treatment. Therefore, the method of the research is effective. Then, the result of questionnaire showed that the students gave positive responses toward the use of songs in learning interdental pronunciation and they felt enjoyed, pleasant and motivated. They were able to pronounce interdental words, but they still needed efforts to get used to. The conclusion of this research is the implementation of songs in learning interdental pronunciation can give a significant effect to the students. It is effective to make them interested, enjoyed and comfortable in learning pronunciation. By using song, they are not only able to improve pronunciation, but also improve listening skill and vocabulary mastery.